(untitled) (Colombia Medica, 2024)
Background: The Yang Tobin Index (Y/T) is a simple and objective measure to predict successful extubation. There are no Colombian studies supporting the use of Y/T as a predictor of successful ventilator weaning. Objective: To estimate the sensitivity and specificity of Y/T as predictor of weaning and to valuate the association with clinical and socio-demographic characteristics in adult patients at the intensive care unit. Methods: Retrospective study. We analyzed a database of 332 records of patients under mechanical ventilation (MV) for more than 48 hours, from January 2006 to December 2007, with spontaneous breathing trial and measurement of Y/T before extubation. Results: The sensitivity of Y/T was 98.6%, specificity 9.6%, positive predictive value 85.4%, egative predictive value 55.5%. The cumulative incidence of successful extubation was 84%. The greater incidence of unsuccessful extubation was associated with COPD (46.2%). The MV time period showed a direct proportional relationship with failed extubation (p=0.186). Conclusions: The Y/T index is not a good predictor of success of extubation in the study opulation. No association was found between clinical and sociodemographic characteristics of the opulation, with respect to the sensitivity and specificity of the Y/T as a predictor of success.